Total alkenone concentrations, alkenone SSTs vs. age (Ma) - Maria Athanasiou; Ioanna Bouloubassi; Alexandra Gogou; Vincent Klein; Margarita D Dimiza; Constantine Parinos; Elisavet Skampa; Maria Triantaphyllou (PANGAEA, 2019)
Organic geochemical (alkenones) and micropaleontological (nannofossil) data from the Pissouri South section (PPS) in the island of Cyprus provided a detailed description of the paleoclimatic (sea surface temperature- SST) and paleoenvironmental conditions during the "warm Pliocene" (c. 4.1-3.25Ma) in the EasternMediterranean. We found that the suite of sapropel events recorded in the studied interval took place under conditions of increased SST, enhanced water column stratification and development of a productive deep chlorophyll maximum (DCM), as witnessed by the dominance of Florisphaera profunda species. Such conditions are similar to those prevailing during Quaternary sapropel formation, triggered by freshwater discharges from the N. African margin due to insolation-driven intensification of the African monsoon. The absence of F. profunda in Pliocene sapropels fromcentralMediterranean records highlights the sensitive response of the eastern basin to freshwater perturbations. Comparisons between alkenone and calcareous nannofossil assemblage patterns infer Pseudoemiliania lacunosa as the main alkenone producer in sapropel layers; yet Reticulofenestra spp. contribution cannot be ruled out. The first Pliocene alkenone-SST record in the E. Mediterranean presented here documents the "warm Pliocene" period (~4.1-3.25 Ma) characterized by mean SST of c. 26 °C. Distinct SST minima at ~3.9 Ma, 3.58 Ma and between 3.34 and 3.31 Ma, correspond to the MIS Gi16, MIS MG12 and MIS M2 global cooling episodes, before the onset of the Northern Hemisphere glaciation. Our findings imply that the peak of the MIS M2 cooling in the Eastern Mediterranean may be up to ~40 kyrs older than the age attributed before to benthic stable oxygen isotopes records of this event.
Supplement to: Athanasiou, M et al. (2017): Sea surface temperatures and environmental conditions during the “warm Pliocene” interval (~ 4.1–3.2 Ma) in the Eastern Mediterranean (Cyprus). Global and Planetary Change, 150, 46-57, https://doi.org/10.1016/j.gloplacha.2017.01.008